Why perpetrators matter - Austin, Jonathan (Contesting torture, 2023)
How do the experiences of perpetrators contest our usual understanding of torture? This chapter explores that question by engaging with the lived, quotidian, and experiential reality of perpetrating acts of extreme violence. It does so by drawing on primary source testimony from torturers, as well as a series of longitudinal interviews carried out with Syrian perpetrators of torture. That material is used to query the degree to which 1) torture is formally ‘trained for’ in most settings, 2) ‘ordered’ by hierarchical authorities in most cases, and 3) something that torturers willingly engage in. While the chapter argues that the experience of perpetrating makes our understanding of violence far more complex, raising serious questions as to whether current mechanisms of ‘holding-to-account’ are suitable, it also argues that engaging with the figure of the perpetrator also provides new and potentially valuable insights into how we might prevent its emergence in the future.